2014
DOI: 10.1002/2014jg002730
|View full text |Cite
|
Sign up to set email alerts
|

Siberian tundra ecosystem vegetation and carbon stocks four decades after wildfire

Abstract: Tundra ecosystem fire regimes are intensifying with important implications for regional and global carbon (C) and energy dynamics. Although a substantial portion of the tundra biome is located in Russia, the vast majority of accessible studies describe North American tundra fires. Here we use field observations and high-resolution satellite remote sensing observations to describe the effects of wildfire on ecosystem C pools and vegetation communities four decades after fire for a tundra ecosystem in northeaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 67 publications
(133 reference statements)
2
26
0
Order By: Relevance
“…Loranty et al . () found that while some of the best‐documented tundra fires are located in Alaska, a large proportion of global tundra fires actually happen in Russia, with an average annual area burned of 331 200 ha/yr in Russia versus 21 400 ha/yr in Alaska for 1950–2011. Beck et al .…”
Section: Landscape Changesmentioning
confidence: 97%
See 1 more Smart Citation
“…Loranty et al . () found that while some of the best‐documented tundra fires are located in Alaska, a large proportion of global tundra fires actually happen in Russia, with an average annual area burned of 331 200 ha/yr in Russia versus 21 400 ha/yr in Alaska for 1950–2011. Beck et al .…”
Section: Landscape Changesmentioning
confidence: 97%
“…Severe fire seasons in Alaska in 2004 (2.7 M ha burn area) and 2015 (2.1 M ha), in Canada in 2015 (4.0 M ha), and in 2012 in Russia (30 M ha) have led to concern of increased fire frequency in response to climate warming (Kasischke et al, 2010). Loranty et al (2014) found that while some of the bestdocumented tundra fires are located in Alaska, a large proportion of global tundra fires actually happen in Russia, with an average annual area burned of 331 200 ha/yr in Russia versus 21 400 ha/yr in Alaska for 1950-2011. used MODIS imagery to calculate the deciduous fraction of burn scars and normalised burn ratio, along with maps of burned areas, albedo and forest biomass, to conclude that more severely burned areas in interior Alaska since the 1950s have shifted toward greater deciduous biomass. An assessment of vegetation succession along the century-scale chronosequence of tundra fire disturbances from 1880 to 2007 manually interpreted using satellite imagery from arctic Alaska found that tundra fires facilitated shrub expansion (Jones et al, 2013b).…”
Section: Landscape Changesmentioning
confidence: 99%
“…At the same time, loss of labile carbon coupled with microbial community and abiotic changes may limit decomposition following fire (Taş et al 2014). Recovery of vegetation and soil accumulation after fire can promote permafrost aggradation enabling recovery of active layer depths to pre-fire conditions (Mackay 1995, Viereck et al 2008, Rocha et al 2012, Loranty et al 2014. In the discontinuous zone, permafrost is often thermally protected by denser vegetation canopies and deeper soil organic layers, meaning disturbance that removes these insulating layers may lead to greater thawing of permafrost (Jorgenson et al 2010).…”
Section: Fire Disturbance-permafrost Interactionsmentioning
confidence: 99%
“…Also, fire events in the boreal forest have been studied more rigorously than tundra fires, partly due to the tundra's extreme environmental conditions . However, with the recent availability of observational data of global fire disturbances, tundra fires have started to receive considerable attention , Liu et al 2014, Loboda et al 2013, Loranty et al 2014, as these fires can play a significant role in global positive climate feedback mechanisms (Bret-harte et al 2013) and perturbations to ecosystem processes . Despite this, existing studies of tundra fires suffer from spatially restricted paleofire records as well as short observational fire records (Stocks et al 1998(Stocks et al , 2003, which limit a comprehensive understanding of the spatial variability of tundra wildfire characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%